PENINGKATAN KETERSEDIAAN DAN SERAPAN FOSFOR PADA PEMBIBITAN KELAPA SAWIT MAIN NURSERY DENGAN APLIKASI KOMPOS TANDAN KOSONG KELAPA SAWIT DAN JENIS PUPUK P PADA TANAH LATOSOL - Pauliz Budi Hastuti; Sri Manu Rohmiyati (AGROISTA : Jurnal Agroteknologi, 2019)
This study aims to determine the effect of empty fruit bunches (efb) compost, Phosphate solubilizing bacteria (PSB), lime and various of P fertilizer in order to increase of P availability and P uptake in the main nursery oil palm seedlings in latosols. The experiment was conducted by using a factorial design, arranged in a completely randomized design. The first factor was the application of efb compost: without efb compost, efb compost, PSB and lime. The second factor was the various of P fertilizer: SP-36, RP, guano and (NPKMg + dolomit) as a control. The results showed that guano fertilizer in various combinations has the highest role in increasing the availability of P in the soil. The highest levels of P leaves and P stems are produced by administration of guano fertilizer in various combinations. P uptake of leaf showed almost the same value in all combinations of treatments except the combination treatment of inorganic fertilizers with PSB produced the lowest value. The highest uptake of P-stem was shown by giving efb compost combined with guano or SP36 fertilizer or inorganic fertilizer. While the lowest P content and P-uptake of the stem is indicated by inorganic fertilizer treatment. The highest growth of palm oil seedlings is produced by a combination of efb compost with all types of P fertilizers or inorganic fertilizers. Provision of PSB with inorganic fertilizer resulted in the lowest growth of oil palm seedlings. Keywords: P uptake, P available, main nursery, efb compost, latosol.